TRANSFORMASI GENETIK DAN EKSPRESI MUTAN SUCROSE PHOSPHATE SYNTHASE PADA TANAMAN TOMAT - Fibriani, Suwinda; Agustien, Inyana Dwi; Sawitri, Widhi Dyah; Sugiharto, Bambang (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
Genetic Transformation and Expression of Sucrose Phosphate Synthase Mutant in Tomato PlantÃ‚Â ABSTRACTSucrose phosphate synthase (SPS) is a key enzyme responsible for sucrose biosynthesis. In its regulation, SPS activity is modulated by an allosteric effector glucose-6-phosphate (G6P) suggested to have an ability to bind SPS N-terminus domain. To understand the role of N-terminus in regulating SPS, the SPS gene was mutated with the deletion of N-terminus domain (Ã¢Ë†â€ N-SPS). The Ã¢Ë†â€ N-SPS gen was transformed into tomato plants with 5% transformation efficiency. Three transgenic tomato plant 4.20, 5.5.1, and 5.10 were obtained and confirmed by PCR analysis. Transgenic tomato expression was characterized by enzymatic analysis. Result showed that the G6P allosteric regulation in transgenic Ã¢Ë†â€ N-SPS had lost and the SPS activity increased by 2-fold compared to non-transgenic plant. This showed that N-terminus domain-deleted SPS could be actively expressed in plant.Ã‚Â Keywords: enzyme, genetic transformation, N-terminus domain deletion, sucrose phosphate synthase, tomatoÃ‚Â ABSTRAKSucrose phosphate synthase (SPS) merupakan enzim kunci yang bertanggung jawab dalam sintesis sukrosa. Dalam regulasinya, aktifitas SPS dipengaruhi oleh alosterik efektor glukosa-6-fosfat (G6P) yang diduga dapat berikatan pada domain N-terminus SPS. Untuk mengetahui peran N-terminus pada regulasi SPS, dilakukan mutasi SPS dengan penghilangan domain N-terminus (Ã¢Ë†â€ N-SPS). Gen Ã¢Ë†â€ N-SPS diinsersi pada tanaman tomat melalui transformasi genetik dengan efisiensi transformasi 5%. Tiga tanaman transgenik tomat (event4.20; 5.5.1; dan 5.10) didapatkan dan positif terkonfirmasi melalui analisis PCR. Ekspresi mutan dikarakterisasi melalui analisis enzimatik. Hasil menunjukkan bahwa tanaman tomat transgenik Ã¢Ë†â€ N-SPS tidak dipengaruhi regulasi alosterik G6P dan aktifitas SPS 2 kali lipat lebih tinggi daripada tanaman bukan transgenik. Ini menunjukkan bahwa SPS dengan delesi domain N-terminus dapat terekspresi aktif pada tanaman. Ã‚Â Kata Kunci: delesi domain N-terminus, enzim, sucrose phosphate synthase, tomat,Ã‚Â transformasi genetikÃ‚Â